Impact of minimally invasive surgery in the treatment of esophageal cancer - Italo BRAGHETTO M; Gonzalo CARDEMIL H; Carlos MANDIOLA B; Gonzalo MASIA L; Francesca GATTINI S. (ABCD: Arquivos Brasileiros de Cirurgia Digestiva, 2014)
BACKGROUND: Surgical treatment of esophageal cancer is associated to a high morbidity and mortality rate. The open transthoracic or transhiatal esophagectomy are considerably invasive procedures and have been associated to high rates of complications and operative mortality. In this way, minimally invasive esophageal surgery has been suggested as an alternative to the classic procedures because would produce improvement in clinical longterm postoperative outcomes. AIM: To assess survival, mortality and morbidity results of esophagectomy due to esophageal cancer submitted to minimally invasive techniques and compare them to results published in international literature. METHOD: An observational, prospective study. Between 2003 and 2012, 69 patients were submitted to a minimally invasive esophagectomy due to cancer. It was recorded postoperative morbidity and mortality according to the Clavien-Dindo classification. The survival rate was analyzed with the Kaplan-Meier method. The number of lymph nodes obtained during the lymph node dissection, as an index of the quality of the surgical technique, was analysed. RESULTS: 63.7% of patients had minor complications (type I-II Clavien Dindo), while nine (13%) required surgical re-exploration. The most common postoperative complication corresponded to leak of the cervical anastomosis seen in 44 (63.7%) patients but without clinical repercusion, only two of them required reoperation. The mortality rate was 4.34%, and reoperation was necessary in nine (13%) cases. The average survival time was 22.59±25.38 months, with the probability of a 3-year survival rate estimated at 30%. The number of resected lymph nodes was 17.17±9.62. CONCLUSION: Minimally invasive techniques have lower morbidity and mortality rate, very satisfactory lymphnodes resection and similar long term outcomes in term of quality of life and survival compared to results observed after open surgery.